Auditoría de aplicaciones al sistema contable Sofadcon. - Pinta Ullauri, Jessica Graciela (My University, 2018)
The present investigation is based on the elaboration of an audit of quality application made to the SOFADCON accounting system managed by the Provincial Board of the Red Cross of El Oro which required a review of its accounting software under standards and guidelines of the norm ISO 25010 based on the characteristics of Usability, Functionality, Security, using the methodology of audit to computer systems, in which there are three phases 1. Planning, where it goes from the origin of the audit, preliminary start-up visit, general data of the company, planning of each activity and the budget 2. Execution, the tests described in the planning are carried out, the evaluation to each one of the characteristics that was previously selected for this investigation and the obtaining of the final results, 3 The Opinion in this part is made known the observations the breaches and conformities that have been found in the area the audit as well as the opinión.
.La presente investigación está basada en la elaboración de una auditoría de aplicación de calidad realizada al sistema contable SOFADCON que maneja la Junta Provincial de la Cruz Roja de El Oro la cual requería de una revisión de su software contable bajo estándares y lineamientos de la norma ISO 25010 en base a las características de Usabilidad, Funcionalidad, Seguridad, usando la metodología de auditoría a sistemas computacionales, en la cual se tiene tres fases 1. La planeación, donde se va desde el origen de la auditoria, visita preliminar de arranque, datos generales de la empresa, planeación de cada actividad y el presupuesto 2. La Ejecución, se realiza las pruebas descritas en la planeación la evaluación a cada uno de las características que se seleccionó previamente para esta investigación y la obtención de los resultados finales, 3. El Dictamen en esta parte se da a conocer las observaciones los incumplimientos y conformidades que se hayan encontrado al realizar la auditoria así como el dictamen.
Keywords: AUDITORÍA DE CALIDAD; SEGURIDAD; CALIDAD DEL SOFTWARE; SOFTWARE CONTABLE; USABILIDAD; FUNCIONALIDAD; ISO 25010